FAMILIARITY OF WORDS IN THE PRODUCTION OF THE CORRECT PRONUNCIATION: HELPFUL OR NOT? - Desianto Fajar Wibisono; Wuryani Hartanto; Cecilia Titiek Murniati (Celt: A Journal of Culture, English Language Teaching & Literature, 2004)
Language is the major instrument of human beings to communicate with one another. This means that the primary role of language is as an instrument in information exchange among people. Because language is primarily spoken, a speaker should pay attention to his or her pronunciation in order to avoid misunderstanding. When conducting a research on the problem of incorrect pronunciation of some specific English consonants in the Faculty of Letters Soegijapranata Catholic University Semarang, the researcher found a unique case in relation with familiarity of the pronunciation among the respondents. In his research, the researcher used a pronunciation test consisting of words containing the problematic consonants and the respondents were some of the fist year students of the Faculty of letters Soegijapranata Catholic University. The words were taken from the most familiar English to the less familiar English words to the respondents. The results are quite surprising because the familiar words are not always pronounced correctly and the less familiar words are not always pronounced incorrectly. What makes this case happen? What are the factors influencing the respondents performance leading to correct or incorrect pronunciation in relation in relation with their degree of familiarity to the words given? This article will discuss the problems and find out the factors influencing the respondents pronunciation.